Perceived Organizational Support on Affective Organizational Commitment of Ministry of State Secretariat’s Civil Servants - Kosasih, Fajar Gumilang; Rizan, Mohamad; Handaru, Agung Wahyu (Interdisciplinary Social Studies, 2022)
Since President Soekarno's election in 1957, there has been discussion about relocating the capital city. Several factors contributed to the change in the capital city, and East Kalimantan was chosen as the new capital city because it met several criteria. The Ministry of State Secretariat is one of the Ministries that became a partner in relocating the Capital City. Socialization will occur regarding the scheme or design for the transfer of employees from the Ministry of State Secretariat. This study aimed to determine how Perceived Organizational Support (POS) affected Affective Organizational Commitment (AOC) in civil servants at the Ministry of State Secretariat. The research used quantitative approach and a cross-sectional study design. This study's sample size was 160 civil servants from the Ministry of State Secretariat. Simple linear regression analysis was used to analyze the data in this study. The results show that perceived organizational support positively and significantly affects affective organizational commitment. The regression analysis test yielded a regression coefficient value of 0.726. The R Square value of 0.465 indicates that the perceived organizational support variables can explain 46,5% of the affective organizational commitment variable, while other variables explain the rest. Human resource practitioners in the Ministry of State Secretariat should strengthen perceived organizational support and affective organizational commitment.